A comparative evaluation of the successes and challenges of the antiretroviral therapy adherence clubs in the Helderberg District of the Western Cape Province, South Africa - Klocke, Marina (Stellenbosch : University of Stellenbosch, 2016)
Thesis (MFamMed)--Stellenbosch University, 2015.